Downregulation of the Vitamin D Receptor Regulated Gene Set in the Hippocampus After MDMA Treatment - Petschner, Peter; Balogh, Noemi; Adori, Csaba; Tamasi, Viola; Kumar, Sahel; Juhasz, Gabriella; Bagdy, Gyorgy (Frontiers in Pharmacology, 2018)
The active ingredient of ecstasy, ±3,4-methylenedioximethamphetamine (MDMA), in addition to its initial reinforcing effects, induces selective and non-selective brain damage. Evidences suggest that the hippocampus (HC), a central region for cognition, may be especially vulnerable to impairments on the long-run, nevertheless, transcription factors that may precede and regulate such chronic changes remained uninvestigated in this region. In the current study, we used gene-set enrichment analysis to reveal possible transcription factor candidates responsible for enhanced vulnerability of HC after MDMA administration. Dark Agouti rats were intraperitoneally injected with saline or 15 mg/kg MDMA. Three weeks later HC gene expression was measured by Illumina whole-genome beadarrays and gene-set enrichment analysis was performed with MSigDB transcription factor sets. The number of significantly altered genes on the genome level (significance<0.001) in up/downregulated sets was also counted. MDMA upregulated one, and downregulated 13 gene sets in the HC of rats, compared to controls, including Pax4, Pitx2, FoxJ2, FoxO1, Oct1, Sp3, AP3, FoxO4 and vitamin D receptor (VDR)-regulated sets (q-value<0.05). VDR-regulated set contained the second highest number of significantly altered genes, including among others, Camk2n2, Gria3 and Grin2a. Most identified transcription factors are implicated in the response to ischemia confirming that serious hypoxia/ischemia occurs in the HC after MDMA administration, which may contribute to the selective vulnerability of this brain region. Moreover, our results also raise the possibility that vitamin D supplementation, in addition to the commonly used antioxidants, could be a potential alternative method to attenuate MDMA-induced chronic hippocampal impairments.